2012
DOI: 10.1084/jem.20111910
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of KRAS mutant tumors by HSP90 inhibitors involves degradation of STK33

Abstract: HSP90 inhibition depletes STK33 in KRAS mutant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 59 publications
2
63
1
1
Order By: Relevance
“…It has been reported that killing of mutant KRAS cancer cells by the HSP90 inhibitor 17-AGG or PU-H71 involves degradation of the serine/threonine kinase STK33 (6). However, degradation of STK33 appeared less likely to be involved in AUY922-induced ER stress-mediated apoptosis of mutant KRAS colon cancer cells, as treatment with AUY922 did not cause any significant change in the expression of STK33 in the cells (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that killing of mutant KRAS cancer cells by the HSP90 inhibitor 17-AGG or PU-H71 involves degradation of the serine/threonine kinase STK33 (6). However, degradation of STK33 appeared less likely to be involved in AUY922-induced ER stress-mediated apoptosis of mutant KRAS colon cancer cells, as treatment with AUY922 did not cause any significant change in the expression of STK33 in the cells (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 86%
“…For example, only depletion of the entire STK33 protein through HSP90 inhibition, but not selective inhibition of STK33's enzymatic activity was able to reproduce the impressive effects of RNA interference-mediated knockdown, suggesting different functions of STK33 are involved in the synthetic lethal interaction with oncogenic KRAS. 46,47 Here we present a different strategy named synthetic lethal vulnerability. Whereas inhibition of the alt-NHEJ pathway has no effect in KRAS mutant cells, it is able to sensitize malignant cells to genotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…A particular molecular chaperone of interest is heat shock protein 90 (Hsp90), which has been shown to support aberrant expression of key oncoproteins such as ALK (anaplastic lymphoma kinase), BCR-ABL (break point cluster-Abelson tyrosine kinase) BRAF (serine/threonine-protein kinase B-Raf), CDK4 (cyclindependent kinase 4), CRAF (serine/threonine-protein kinase C-Raf), HER2 (human epidermal growth factor receptor 2), JAK2 (Janus kinase 2), KIT (Mast/stem cell growth factor receptor, protooncogene c-Kit) MET (mesenchymal epithelial transition factor), and STK33 (serine/threonine kinase 33) [13][14][15][16][17]. Initial attempts to target Hsp90 with inhibitors that resemble the structure of the natural products geldanamycin and radicicol indicated that successful targeting of the chaperone could yield therapeutic benefit at the clinical level, but such compounds are plagued by unfavorable toxicity profiles that limit achievable doses [18,19].…”
Section: Introductionmentioning
confidence: 99%